Trypauchen vagina (Bloch & Schneider, 1801) a new established species in the Southwestern Atlantic - Trevisan, João Pedro (2023)
Trypauchen vagina (Bloch & Schneider, 1801) is a goby that lives burrowed into the substrata feeding on small invertebrates. It is native to the Indo-pacific region, ranging from Kuwait to China. Recently, this fish has been reported outside the original range of distribution, being found in the Mediterranean Sea, and more recently in the northeastern Brazilian coast. The Mediterranean reports are usually associated with Lessepsian migration, while the reports from Brazil are possibly related to ballast water transportation. In the present work, we provide eight new records from southeastern Brazilian coast, all made in São Paulo state, far from the first record. These additional records raised concern since the presence of an alien species could implicate in environmental and economic losses. Thus, we decide to model the environmental suitability for this goby in the Brazilian coast, specially focusing on major ports, usually places with high ballast water propagule pressure. In addition, an analysis of the suitability in the Red Sea was also made, to verify the hypothesis of Lessepsian migration. The results revealed that temperature and primary productivity are among the most important parameters for the presence of T. vagina, also indicating a high environmental suitability for this species in the Red Sea and Brazilian coast, especially in southeastern region, where the new records were made. Due to the number of collected individuals, it is hard to affirm that this taxon presents a self-sustaining population in Brazilian waters, but the several registers, in different locations and different life stages point to an establishment of the species in this new region. This population status allied with a high environmental suitability is alarming and should motivate new studies concerning T. vagina in Brazilian waters.